Self-nanoemulsions loaded with dihydromyricetin: Insights to their formulation stability. (November 2020) - Chen, Lei; Lin, Xiujun; Yao, Maojun; Teng, Hui
Abstract: The aim of the present study is to develop and optimize self-nanoemulsifying drug delivery systems (SNEDDS) to improve the stability and solubility of dihydromyricetin (DHM). Solubility of DHM was tested in various vehicles to select proper combinations of components; ternary phase diagrams were constructed to investigate the proportion of formula of emulsion. Based on the results of emulsification grade and thermodynamic stability, the DHM-SNEDDS was formed by using medium chain triglycerol (MCT) as oil phase; Cremophor-RH40 as surfactant; and glycerol as co-surfactant. The particle size distribution, zeta potential, and polydispersity index were analyzed to be 56.54 ± 0.36 nm, −5.21 ± 0.54 mV and 0.312 ± 0.08, respectively. The maximum observed drug loading was 45 mg/kg, the obtained loading efficiency was extremely good. The in vitro release profile of DHM-SNEDDS was found significant in comparison to the plain DHM suspension. Hence, SNEDDS could be a promising strategy to overcome the poor water solubility and short biological half-life of DHM for further application in functional foods and beverage industry. Graphical abstract: Image 1 Highlights: Dihydromyricetin (DHY) was encapsulated in an O/W emulsion with high efficiency. Edible emulsions possess promising potential to encapsulate DHM. Emulsions loaded with DHM could promote drug release.